2019
DOI: 10.1037/xge0000543
|View full text |Cite
|
Sign up to set email alerts
|

Wise reasoning benefits from emodiversity, irrespective of emotional intensity.

Abstract: The role of emotions in wise reasoning is not well understood. On the one hand, work on emotional regulation suggests downregulating intense emotions may lead to wiser reasoning. On the other hand, emerging work suggests recognizing and balancing emotions provides critical insights into life experiences, suggesting an alternative path to wiser reasoning. We present a series of observational, diary, and experimental studies (N = 3,678) addressing these possibilities, examining how wisdom-related characteristics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 127 publications
(217 reference statements)
5
52
0
Order By: Relevance
“…As such, the present findings are in line with prior work on emotional and affective complexity (e.g., Carstensen et al, 2000;Tobacyk, 1980), especially that which has established a strong relationship between valence-focused or bipolar affect, lower emotional granularity (Barrett, 1998(Barrett, , 2004Feldman, 1995), and coping and health (Zautra et al, 2000(Zautra et al, , 2001(Zautra et al, , 2005. Similarly, these findings echo work on the diversity of emotional experience, or 'emodiversity' (Quoidbach et al, 2014), which has been linked to positive mental and physical health outcomes (Grossmann et al, 2019;Ong et al, 2018;Quoidbach et al, 2014;Werner-Seidler et al, 2018). Emodiversity is conceptually based on the Shannon (1948) diversity index, H (although see Benson et al, 2018;Brown & Coyne, 2017), which also forms the basis for the positive and negative diversity coefficients computed in the present study .…”
Section: Discussionsupporting
confidence: 56%
“…As such, the present findings are in line with prior work on emotional and affective complexity (e.g., Carstensen et al, 2000;Tobacyk, 1980), especially that which has established a strong relationship between valence-focused or bipolar affect, lower emotional granularity (Barrett, 1998(Barrett, , 2004Feldman, 1995), and coping and health (Zautra et al, 2000(Zautra et al, , 2001(Zautra et al, , 2005. Similarly, these findings echo work on the diversity of emotional experience, or 'emodiversity' (Quoidbach et al, 2014), which has been linked to positive mental and physical health outcomes (Grossmann et al, 2019;Ong et al, 2018;Quoidbach et al, 2014;Werner-Seidler et al, 2018). Emodiversity is conceptually based on the Shannon (1948) diversity index, H (although see Benson et al, 2018;Brown & Coyne, 2017), which also forms the basis for the positive and negative diversity coefficients computed in the present study .…”
Section: Discussionsupporting
confidence: 56%
“…Being a wise person in general (i.e., average cross-diary scores) had limited power in predicting emotions or forgiveness in conflicts above and beyond that person's expression of wisdom in a concrete situation. Additionally, re-analysis of the diary data also revealed that on some of the wisdom-related characteristics, the situation rather than trait scores were related to emotionally rich and balanced representation of the situation (Grossmann et al 2019;Study 2). Figure 3 summarizes observational and experimental evidence about variability in practical wisdom.…”
Section: Cross-situational Variability In Wisdom: Evidence From Obsermentioning
confidence: 98%
“…Some of the recent work appears to suggest that cultural differences in essentialism of the self extend to wisdom as well. Grossmann et al (2019) surveyed participants from the USA, Canada, China, and Russia and found that people from more individualistic cultures (Canada/ the USA) held more fixed beliefs about wisdom than people from more collectivistic cultures (China/Russia) (see Fig. 1).…”
Section: Theories About Malleability Of Wisdom Lay Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…By naming felt qualities, such as love, warmth, acceptance, ease, tenderness, safety, feeling seen, gratitude, inner freedom, openness, peace, feeling at home, joy, restfulness, etc., practitioners begin to cultivate an increasing awareness of, and receptivity to, a full spectrum of their innate capacities of care. The capacity to name a full spectrum of caring qualities is analogous to the concept of emotion granularity in affective science, in which labeling emotions with increasing precision and specificity leads to a richer emotional life characterized by greater well-being, discernment, and flexibility around emotional responding (Barrett et al, 2001;Quoidbach et al, 2014;Kashdan et al, 2015;Grossmann et al, 2019). We hypothesize that increasing granularity for caring qualities should lead to an increasing ease with which to notice, access and draw upon such qualities.…”
Section: Meditation 1: Field Of Carementioning
confidence: 99%